FINANCIAL PERFORMANCE ANALYSIS BEFORE AND AFTER THE IMPLEMENTATION OF FINANCIAL MANAGEMENT PATTERNS OF REGIONAL GENERAL SERVICES AGENCY AT CUT MEUTIA REGIONAL GENERAL HOSPITAL, ACEH UTARA REGENCY - Rolinda, Cut; Naz’aina, Naz’aina; Khaddafi, Muammar (RADJA PUBLIKA, 2022)
This study analyzed differences in financial performance before and after the implementation of the Financial Management Pattern of the Regional Public Service Agency (PPK-BLUD) at Cut Meutia Public Hospital, North Aceh Regency. Financial performance was proxied by the ratio of profitability, liquidity, solvency, and activity. The periods used were 2012-2015 (Before KDP-BLUD) and 2016-2019 (After KDP-BLUD). This study used secondary data in the form of quantitative data. The data analysis method used was Paired T-Test. The results showed that in financial performance ratios, there were significant differences in the ratio of profitability, liquidity, and activity before and after the implementation of PPK-BLUD, but the solvency ratio did not differ before and after the implementation of PPK-BLUD at Cut Meutia Hospital, North Aceh Regency.